The Effect of Graphic Organizers and Instructional Scaffolding on Argumentative Writing Performance Among TESL Undergraduates - Jayasari Lingaiah (2019)
The present study investigated the effect of graphic organizers and instructional scaffolding on argumentative writing performance among TESL undergraduates. The study employed a quasi-experimental research using the pre-test and post-test design involving 90 TESL undergraduates being placed equally in three different groups underwent lessons on argumentative essay writing using different delivery modes, modes comprising of four stages of learning for a duration of four weeks. During the intervention period, three small groups of TESL undergraduates from the GOIS and GONI delivery modes were video-recorded to investigate on how they communicate in their groups. After the intervention, a semi-structured interview was carried out. A total of 9 students (GOIS, n=3; GONI, n=3; NGNI, n=3) were interviewed and the interviews were audio-recorded. The one-way ANCOVA was used to analyse the argumentative writing performance among the TESL undergraduates. The percentages were used to compare the overall percentages of Comm between the GOIS and GONI delivery modes while the qualitative data from the semi-structured interview of the three delivery modes were analysed using the constant comparative approach. Results showed that the group which underwent the GOIS delivery mode performed significantly better in the overall argumentative essay writing performance (p<.05) compared to their counterparts in the GONI and NGNI delivery modes. Additionally, in terms of the overall frequency of conjunctions and overall frequency of argumentative elements, the results indicated that both the GOIS and GONI groups performed significantly better (p<.05) than the NGNI group. In terms of overall percentages of , the GONI group outperformed the GOIS group. The findings from the semi-structured interview revealed that the GOIS group experienced learning better compared to the GONI and NGNI groups. The research confirmed that the GOIS and GONI delivery modes are effective in enhancing argumentative writing performance among TESL undergraduates. In line with this, the research ends with a recommendation for educators to adopt these delivery modes in t argumentative writing skills are enhanced. (Abstract by Author)